ACINAR CELL CARCINOMA OF PANCREAS IN A CHILD: A RADIOLOGICAL PERSPECTIVE - Husen, Yousuf; Saeed, Muhammad Anwar; Siddiqui, Saad (Journal of Ayub Medical College Abbottabad, 2015)
Acinar cell carcinoma is a rare tumour arising from pancreatic acinar cells. Typical radiological patterns associated with it may suggest the unusual diagnosis even before final confirmation by histopathology. We present a case of an 8 year old boy who presented to clinic with symptoms of abdominal pain without associated jaundice or vomiting. Imaging revealed an atypical mass arising from head of the pancreas. Histopathology confirmed the diagnosis of acinar cell carcinoma. An idea about atypical and rare pancreatic masses is necessary to help direct the diagnosis and guide the pathologist for suspecting atypical pathology.